Neoliberal Sexual Humanitarianism and Story-Telling: The case of Somaly Mam - Hoefinger, Heidi (Anti-Trafficking Review, 2016)
Stories of trafficking into the sex industry in Cambodia are a popular feature in local and international media, academic and development literature, policy and humanitarian debates, social and political discourse, and NGO interventions. These stories are powerful for their ability to evoke deep emotions and outrage from their intended audiences. However, they are equally powerful for the ways in which they can cause harm—namely to already marginalised populations of migrants and people involved in the sex trade either by choice, circumstance or coercion. One of the most contentious contemporary trafficking stories is that of the controversial case of Somaly Mam—the self-declared ‘sex slave’ turned ‘modern-day hero’. This paper outlines Mam’s prolific trajectory of self-representation according to the tropes of sexual humanitarianism and argues that these narratives helped to set in motion one of the most lucrative, and in many ways, most exploitative and problematic anti-trafficking endeavours in Cambodia, to date. The paper concludes with offering suggestions for how the anti-trafficking industry might better address real cases of trafficking and exploitation by focusing on structural violence and systemic injustice rather than on sensationalised humanitarian rhetoric, which can perpetuate harms.